Relationship Between Institutional Ownership and Financial Standing and Value of Stock Exchange Listed Companies - Szewc-Rogalska, Alina (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This study aims to analyze the relations between the institutional investors’ share in the ownership structure and the operation of publicly-traded companies, in particular, their financial standing and value. It presents the most significant reasons and mechanisms how institutional investors affect the chosen aspects of operation of portfolio companies. The findings of the selected international and domestic research pertaining to the impact of institutional investors on the development of the financial standing and value of companies were discussed. Moreover, the creation of value of companies and value for shareholders in the Polish capital market has been assessed. It was found that positive, statistically-significant relations between the institutional ownership and the financial standing and value of companies are usually seen in the developed capital markets. It pertains mainly to the markets featuring a high degree of institutional ownership development. The research in the Polish capital market has not resulted in any implicit outcomes, but there is an increasing amount of empirical evidence demonstrating certain relations.